Sustaining Oral Communication: A Quasi-Experimental Study of Project-Based Learning and Speaking Fluency in EFL Contexts - Siswoyo Siswoyo (Universitas Muhammadiyah Lampung, 2025)
Speaking fluency is a crucial component of oral communication for English as a Foreign Language (EFL) learners, particularly in higher education where students are required to express ideas clearly and continuously. However, many EFL students experience limited fluency due to restricted opportunities for extended oral practice and the dominance of form-focused instruction. This study aims to examine the effect of Project-Based Learning (PBL) on undergraduate EFL students’ speaking fluency. A quantitative quasi-experimental design was employed involving 60 second-semester students at Universitas Muhammadiyah Pringsewu (UMPRI), divided into an experimental group (n = 30) and a control group (n = 30). The experimental group received instruction through Project-Based Learning, while the control group was taught using conventional speaking instruction. Data were collected through pre-test and post-test speaking tasks and analyzed using paired-sample and independent-sample t-tests. Speaking fluency was measured based on speech rate, pause frequency, and length of continuous utterances. The results showed that the experimental group’s mean score increased from 62.40 to 78.15, while the control group improved from 63.10 to 69.30. Statistical analysis revealed a significant difference in post-test scores between the two groups (t = 5.36, p < 0.05). These findings indicate that Project-Based Learning significantly enhances EFL students’ speaking fluency and provides effective opportunities for sustained oral communication in higher education contexts.